1995
DOI: 10.1037/0021-843x.104.1.123
|View full text |Cite
|
Sign up to set email alerts
|

EEG concomitants of hypnosis and hypnotic susceptibility.

Abstract: Electroencephalograph (EEG) measures described high- and low-hypnotizable participants in terms of 3 conditions: an initial baseline period; baselines preceding and following a standard hypnotic induction; and during the induction. The following results were obtained. 1. High and low-hypnotic susceptible participants displayed a differential pattern of EEG activity during the baseline period, characterized by greater theta power in the more frontal areas of the cortex for the high-susceptible participants. 2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 38 publications
7
74
1
4
Order By: Relevance
“…However, they were able to show that increased theta power is also observed at frontal locations. This effect of increased theta power in frontal regions in highs at baseline was replicated by Graffin, Ray and Lundy (1995). Increased frontal-central theta is associated with greater attentional focus and improved performance supporting the notion of better attentional performance in highs at baseline, and greater attentional focus under hypnosis (Schacter, 1977).…”
Section: Frontal Executive Functions and Hypnotic Suggestibilitysupporting
confidence: 50%
“…However, they were able to show that increased theta power is also observed at frontal locations. This effect of increased theta power in frontal regions in highs at baseline was replicated by Graffin, Ray and Lundy (1995). Increased frontal-central theta is associated with greater attentional focus and improved performance supporting the notion of better attentional performance in highs at baseline, and greater attentional focus under hypnosis (Schacter, 1977).…”
Section: Frontal Executive Functions and Hypnotic Suggestibilitysupporting
confidence: 50%
“…Several authors reported an increase of the power in the theta frequency band (Tebecis et al, 1975;Crawford, 1990;Sabourin et al, 1990;Graffi n et al, 1995;De Pascalis et al, 1998). In contrast to meditation, increased beta activity in the right occipital cortex was measured (Ulett et al, 1972) and a signifi cant power increase in the right parietal region .…”
Section: Hypnosismentioning
confidence: 95%
“…In the literature, the relevance of hypnotisability for the occurrence of trance phenomena or for long-lasting effects of hypnosis is a matter of debate [see, for example 23]. While some authors report that at least some physiological correlates of hypnosis depend strongly on hypnotisability [e.g., 24], others do not find such a relationship [e.g., 25, 26]. In a recent paper investigating the influence of emotions on cutaneous hypersensitivity, Zachariae et al [27]could only partly replicate previous findings by Laidlaw et al [26]concerning the influence of hypnotisability.…”
Section: Discussionmentioning
confidence: 99%